The Significance of Prolonged and Saddleback Fever in Hospitalised Adult Dengue - Ng, Deborah HL; Wong, Joshua GX; Thein, Tun-Linn; Leo, Yee-Sin; Lye, David C. (PLOS ONE, 2016)
Dengue fever is gaining importance in Singapore with an increase in the number of cases and mortality in recent years. Although prolonged and saddleback fever have been reported in dengue fever, there are no specific studies on their significance in dengue. This study aims to examine the prevalence of prolonged and saddleback fever in dengue as well as their associations with dengue severity. A total of 2843 polymerase-chain reaction (PCR) confirmed dengue patients admitted to Tan Tock Seng Hospital from 2004 to 2008 were included in the study. Sixty-nine percent of them were male with a median age of 34 years. Prolonged fever (fever > 7 days duration) was present in 572 (20.1%) of patients. Dengue hemorrhagic fever (DHF), dengue shock syndrome (DSS) and severe dengue (SD) were significantly more likely to occur in patients with prolonged fever. Mucosal bleeding, anorexia, diarrhea, abdominal pain, nausea or vomiting, lethargy, rash, clinical fluid accumulation, hepatomegaly, nosocomial infection, leukopenia, higher neutrophil count, higher hematocrit, higher alanine transaminase (ALT) and aspartate transaminase (AST), higher creatinine, lower protein and prolonged activated partial thromboplastin time (APTT) were significantly associated with prolonged fever but not platelet count or prothrombin time (PT). Saddleback fever was present in 165 (5.8%). Although DHF and SD were more likely to occur in patients in those with saddleback fever, DSS was not. Compared with prolonged fever, saddleback fever did not show many significant associations except for diarrhea, abdominal pain, clinical fluid accumulation, hematocrit and platelet change, and lower systolic blood pressure. This study demonstrates that prolonged fever may be associated with various warning signs and more severe forms of dengue (SD, DSS, DHF), while saddleback fever showed associations with DHF and SD but not DSS. The presence of prolonged or saddleback fever in dengue patients should therefore prompt detailed evaluation for complications of dengue, as well as early investigation to evaluate for development of nosocomial infection.